Caries Risk Among 15-40 Years Old Patients Visiting Private Dental Institution - A Retrospective Study - N, PRASHAANTHI .; BALASUBRAMANIAM, ARTHI; K.K, SHANTHA SUNDARI. (The journal of contemporary issues in business and government, 2021)
Various models for predicting caries risk have been developed with good results. One such recently developed model is Cariogram. Cariogram systematize the evaluation of various risk factors for caries and recommend targeted preventive intervention based on caries risk. The aim of this study was to evaluate the caries risk among 15-40 years adults in Chennai. A retrospective study was conducted using records of patients visiting private dental college during the month of Feb 2020 to March 2020. A total of 112 case records were retrieved and analysed. Descriptive statistics in terms of frequency distribution was done to present the result. Mean chance to avoid caries was high in 36-40 years (57.8±27.1). Mean bacterial count was high for in the age group 31-35 years (14.6±7.153). Mean susceptibility was high among 21-25 years(23.6±18.8). Mean diet sector was high among 31-35 years(11.6±5.66). The association of age and chances to avoid new caries was p=0.119, circumstances was p=0.386; bacterial sector was p=0.919; susceptibility was p value=0.358 and diet was p=0.513 which was found to be statistically not significant. Males and females of age group 31-35 years have high risk for caries. Young adults have higher risk for caries with no association between age and all five components of cariogram.